Analisis Pengaruh Nilai Evaluasi Dosen Terhadap Kelulusan Mata Kuliah Mahasiswa Universitas Advent Indonesia dengan Decision Tree - Yusran Tarihoran; Timotius Ginting (Syntax Idea)
Analysis of course completion at Universitas Advent Indonesia (UNAI) is an important thing to do. By knowing the course completion of students early, UNAI can take necessary actions to improve students' course completion. This study reveals the influence of lecturer evaluation scores on student course completion in the Web Programming 1, Web Programming 2, and Programming Algorithm 1 courses during the academic years 2020-2021 to 2022-2023. The purpose of this study is to see the influence of lecturer evaluation scores on student course completion in these courses and which competencies most affect student scores. The method used in this study is data mining with the C4.5 decision tree algorithm. The results of this study show that out of 5 competencies tested, 3 competencies affect student course completion. This study uses a confusion matrix evaluation model that produces a prediction accuracy of 80%.